The magic number: Are improved outcomes observed at trauma centers with undertriage rates below 5%?. Issue 4 (October 2018) - Jammula, Shreya; Bradburn, Eric H.; Gross, Brian W.; Cook, Alan D.; Reihart, Michael J.; Rogers, Frederick B.
Abstract : BACKGROUND: The American College of Surgeons Committee on Trauma (ACSCOT) advises trauma centers maintain <5% undertriage rate (UTR), but provides limited rationale for this figure. We sought to determine whether patients managed at Level I/II trauma centers with a UTR less than 5% had improved outcomes compared with centers with greater than 5% UTR. We hypothesized that similar overall adjusted outcomes would be observed at trauma centers in Pennsylvania regardless of their compliance with ACSCOT undertriage recommendation. METHODS: The Pennsylvania Trauma Outcome Study database was retrospectively queried for all trauma patients managed at accredited adult Level I/II trauma centers (n = 27) from 2003 to 2015. Patients with missing data on Injury Severity Score and/or Trauma Activation Status were excluded from the analysis. Institutional UTR were calculated for all trauma centers based on ACSCOT criteria (Injury Severity Score >15; no trauma activation) and were categorized into less than 5% or greater than 5% subgroups. A multilevel mixed-effects logistic regression model assessed the adjusted impact of management at centers with less than 5% undertriage. Statistical significance was set at p less than 0.05. RESULTS: A total of 404, 315 patients from 27 trauma centers met inclusion criteria. Institutional UTRs ranged from 0% to 20.5%, with 15 centers exhibiting UTR less than 5% and 12 centers with UTR greater than 5%. No clinically meaningful difference in unadjusted mortality rate was observed between subgroups (<5% UTR: 5.19%; >5% UTR: 5.20%; p < 0.001). In adjusted analysis, no difference in mortality was found for patients managed at centers with less than 5% UTR compared to those with greater than 5% UTR (adjusted odds ratio, 1.06; 95% confidence interval, 0.85–1.33; p = 0.608). CONCLUSION: Achieving ACSCOT less than 5% undertriage standards appears to have limited impact on institutional mortality. Further research should seek to identify new triage criteria that can be uniformly applied to all trauma centers. LEVEL OF EVIDENCE: Epidemiological study, level III.